Analisis Financial Distress, Audit Delay Dan Opini Audit Terhadap Voluntary Auditor Switching Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Sriwardany Sriwardany; Ratna Sari Dewi (Jurnal Riset Akuntansi dan Bisnis, 2021)
Auditor switch can be implemented mandatory and voluntary. The phenomenon of the voluntary auditor switch is an interesting thing to study. This study aims to analyze the determinants of financial distress, audit delay and auditor opinion on voluntary auditor switches in companies listed on the Indonesia Stock Exchange. This study used secondary data from 31 research samples that were determined purposively. The data is interpreted descriptively and then analyzed using logistic regression with the help of SPSS 23 software. The results of the analysis show that all independent variables do not have a significant effect on voluntary auditor switches in companies listed on the Indonesia Stock Exchange. The influence of these variables is the same, both as a whole and partially on the voluntary auditor switch..